How to build a high-trust workplace : the more your employees trust you, the more engaged they'll be - Reichheld, Ashley; Dunlop, Amelia (MIT Sloan Management Review, 2023)
The authors contend that addressing the question “How much do my employees trust me?” is the real key to employee engagement. They discuss a free tool developed at Deloitte — HX TrustID — that companies can use to gauge employee trust and devise strategies for improving it. They then describe how two organizations — one large, and one small — have used the tool to address leaders’ performance in four areas that contribute to employee trust: humanity, transparency, capability, and reliability.